Authority of the Ministry of Environment in the Investigation of Money Laundering from Environmental Crimes - Daswanto, Daswanto; Manthovani, Reda; Ali, Hatta; Tarson, Eddie; Abdurahmonov, Farhod (Journal of Law, Environmental and Justice, 2025)
This study aims to clarify the jurisdiction of Civil Servant Investigators (hereinafter referred to as PPNS) at the Ministry of Environment in the investigation of money laundering offenses related to environmental crimes. The author initially delineates the power of PPNS inside the Indonesian criminal justice system to provide a complete description. This research constitutes a normative legal analysis. The study's findings demonstrate that the Ministry of Environment has the jurisdiction to investigate money laundering offenses stemming from environmental crimes, particularly following the issuance of Constitutional Court Decision No. 15/PUU-XIX/2021. This decision broadens the investigative authority regarding money laundering, unifies disparate sectoral regulations, and establishes a legitimate legal framework for PPNS, especially within the Ministry of Environment and Forestry, to function as investigative entities in the national strategy against money laundering linked to environmental crimes. The Constitutional Court Decision No. 15/PUU-XIX/2021 significantly alters the framework of investigative authority concerning money laundering offences derived from environmental crimes, by conferring constitutional validity upon PPNS at the Ministry of Environment and Forestry to directly investigate money laundering as a subsequent offence to environmental crimes.